Character Values ​​Education Through Tarek Pukat Dance for UNIKI Performing Arts Education Students - Basri, Novysa; Miftahul Jannah; Umul Aiman; Rudy Juli Saputra; Novita Hidayani; Rizki Rahmad; Aida Fitri (Catharsis, 2025)
The purpose of this study was to determine the character value education in the Tarek Pukat dance of UNIKI Performing Arts education. This study uses a qualitative descriptive method, and a case study approach. Data collection techniques use the stages of observation, interviews and document analysis. With the aim of examining the character values ​​contained in the Tarek Pukat Dance. A qualitative approach with a case study design was used to specifically understand character values in educational praxis through the Tarek Pukat Dance. The results of this study indicate that in the Tarek Pukat dance, the character value education that is seen is in the form of religious, responsibility, tolerance, discipline, cooperation values, humility and this is packaged into character value education in the Tarek Pukat Dance, namely religious values ​​that are born in the Tarek Pukat Dance contain strong religious values, such as patience and perseverance, discipline, humility and responsibility. Social values ​​in the Tarek Pukat Dance such as cooperation, mutual cooperation, humility and tolerance. Cultural values ​​that can be taken from the Tarek Pukat Dance symbolize Acehnese cultural values, such as strength and resilience of local culture and love of the homeland. Aesthetic value: Tarek Pukat Dance also symbolizes aesthetic values, such as beauty and art from local culture. Tarek Pukat dancers in UNIKI performing arts education have and are able to implement the religious values ​​of Tarek Pukat Dance used in religious ceremonies, social events, such as weddings and other events. Cultural events such as festivals have aesthetics, such as art performances